How Should Educational Effects Be Communicated to Teachers?. (August 2021) - Lortie-Forgues, Hugues; Sio, Ut Na; Inglis, Matthew
Research findings regarding the effects of educational interventions—typically reported in units of standard deviations (e.g., Cohen's d )—are often translated into more intuitive metrics before being communicated to teachers. However, there is no consensus about the most suitable metric, and no study has systematically examined how teachers respond to the different options. We conducted two preregistered studies addressing this issue. We found that teachers have strong preferences concerning effect size metrics in terms of informativeness, understandability, and helpfulness. These preferences challenge current research reporting recommendations. Most importantly, we found that different metrics induce different perceptions of an intervention's effectiveness—a situation that could cause teachers to have unrealistic expectations about what a given intervention may achieve. Implications for how educational effects should be communicated are discussed.